Methanol extract of Ligusticum chuanxiong Hort. Rhizome ameliorates bilateral common carotid artery stenosis-induced cognitive deficit in mice by altering microglia and astrocyte activation - Lim, Sehyun; Lim, Chiyeon; Cho, Suin (Frontiers in Pharmacology, 2024)
In traditional Asian medicine, Ligusticum chuanxiong Hort also known as Conioselinum anthriscoides "Chuanxiong", is mainly used for improving blood circulation or for analgesic and anti-inflammatory purposes, but they also have a long history of use for pain disorders in the head and face, such as headache. Despite the possibility that the plant is effective for diseases such as cerebral infarction and vascular dementia (VaD), the mechanism of action is not well understood. To determine if the dried rhizomes of L. chuanxiong (Chuanxiong Rhizoma, CR) methanol extract (CRex) has activity in a VaD mice model. Through network analysis, we confirm that CR is effective in cerebrovascular diseases. In mice, we induce cognitive impairment, similar to VaD in humans, by chronically reducing the cerebral blood flow by performing bilateral common carotid artery stenosis (BCAS) and administering CRex for 6 weeks. We measure behavioral changes due to cognitive function impairment and use immunofluorescence staining to confirm if CRex can inhibit the activation of astrocytes and microglia involved in the inflammatory response in the brain. We quantify proteins involved in the mechanism, such as mitogen-activated protein kinases (MAPK), in the hippocampus and surrounding white matter, and analyze gene expression and protein interaction networks through RNA sequencing to interpret the results of the study. CRex administration rescued cognitive impairment relating to a novel object and inhibited the activation of astrocytes and microglia. Western blotting analysis revealed that CRex regulated the changes in protein expression involved in MAPK signaling such as extracellular signal-regulated kinase (ERK) and p38 mitogenactivated protein kinase (p38). The administration of CRex suppressed approximately 44% of the pathological changes in gene expression caused by BCAS. CRex extract effectively inhibited cognitive impairment caused by BCAS, and the mechanism through which this occurred is inhibited activation of astrocytes and microglia.